Premium for liquidity risk in the interbank market, for a group of emerging economies - Gregoire C., Jorge; Ortiz J., Claudio (Estudios de Administración, 2012)
This article studies the behavior of liquidity premia with data from interbank deposits and swaps, for the period june 2006 to october 2009, thus including the financial crisis. For the USA market the liquidity premium presents a relatively low volatility and an average of 42 annual basis points. For a sample of emerging economies that includes Brazil, Russia, India, China and Chile the liquidity premium is highly volatile and averages in general above 100 basis points. Further the behavior of the liquidity premium is modeled with vector cointegration (Johansen, 1988) and the results indicate that for Brazil, Chile, India, Russia the liquidity premium, the local stock market and foreign exchange rate do cointegrate in a long run equilibrium, and the VECM shows that these endogenous variables are complementary in adjusting the short run deviations from equilibrium; for China is different given the local exchange rate system. These results are also coherent with a refuge hypothesis. For the USA the results show cointegration for liquidity premium, S&P500, and VIX series.